PEMASARAN IDEOLOGI POLITIK ISLAM : ANTARA TUJUAN DAN KENYATAAN - Fathurin Zen (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2013)
Political issues in Indonesia today cannot be separated completely from the affairs ofreligion. Many politicians or political party's campaign cites religious moral messages(jargon) in performing its activities. Some of them make the Islamic ideology as the maintheme and superior political product. People as voters should have a good understanding ofthe meaning of Islamic ideology as a jargon on the one hand, with the values of Islam onpolitical and social in daily activities on the other hand. Fallacy would be done by the peoplefor differentiating Islamic jargon of political commodity and practical life covered byreligious values would cause the voter attitudes no respect toward the deviant politicians andwill eventually turn around to blame the political parties. The question is, should the ideologyof Islam as a political product is packaged and processed into commodities practicaloperational that useful for the voters?